Esophageal atresia - associated anomalies and predictive factors of mortality - Ioana-Valentina Nenciu; Cristina-Adriana Becheanu; Iulia Florentina Ţincu; Ana Maria Brădeanu; Mihaela Bălgrădean (Amaltea Medical Publishing House, 2020)
Introduction. Esophageal atresia (EA), typically occurring with tracheoesophageal fistula (TEF), is one of the most common digestive malformations; 50% of the esophageal atresia cases associate other malformations, syndromes or association of congenital abnormalities. EA is also met in patients with Edwards syndrome, Down syndrome, Di George syndrome and Pierre Robin syndrome. Delayed diagnosis of EA associated anomalies leads to increased morbidity and mortality, especially in patients with two or more associated abnormalities. Our study aims to highlight EA associated anomalies and to evaluate their impact on mortality. Materials and methods. We conducted a retrospective study of all newborns admitted in the Neonatal Intensive Care Unit of "Grigore Alexandrescu" Emergency Clinical Hospital for Children, with the diagnosis of esophageal atresia/ tracheoesophageal fistula (TEF), between January 2013 and December 2018; we evaluated demographic information, clinical manifestation, the ultrasound and radiological results. Our study aimed to highlight AE associated anomalies and to evaluate their impact on mortality. Results. 56 newborns with esophageal atresia/ tracheoesophageal fistula diagnosis were identified. 31 of them were boys, and 22 patients had gestational age (GA) between 32 and 36 weeks. Five newborns came from twin pregnancies. EA/ TEF associated anomalies were identified in 35 patients; the most frequent of those were cardiac anomalies (identified in 25 patients). The association of 3 anomalies from VACTERL spectrum (vertebral, anorectal, cardiac, EA/ TEF, renal and urinary, and limb lesions) was seen in 11 newborns. The estimated risk of death was lightly increased in females and in patients from urban area; the patients with limb anomalies had an estimated risk of death 5 times higher (p = 0.043). Conclusions. EA is a complex pathology both by the malformations and genetic syndromes that can be associated with it, and by the complications that occur in evolution. Antenatal diagnosis of EA and of the associated anomalies, along with multidisciplinary care, represent important measures in order to avoid underdiagnosis of associated problems.